Incidentally discovered Meckel's diverticulum: should I stay or should I go?. Issue 9 (11th August 2020) - Tartaglia, Dario; Cremonini, Camilla; Strambi, Silvia; Ginesini, Michael; Biloslavo, Alan; Paiano, Lucia; Quilici, Francesca; Castagna, Maura; Di Saverio, Salomone; Coccolini, Federico; Chiarugi, Massimo
Abstract : Although histological alterations are more frequent in complicated Meckel's diverticulum (MD), ectopic mucosa and even tumour may be lodged in incidental MD. Complicated MD can be diagnosed before surgery in only 12% of cases. Stapled diverticulectomy has been shown to be a low‐risk surgical procedure. Diverticulectomy is a safe and effective method of treatment of incidentally discovered MD. Abstract: Background: The aim of this study was to assess the indication for surgical treatment of incidentally discovered Meckel's diverticulum (MD) on the basis of clinical and histological features. Methods: The charts of patients undergoing surgery for MD were analysed. Two groups were identified: (1) patients who had incidentally discovered MD resected (incidental MD, IMD) and (2) patients who received first‐line surgery for a complicated MD (CMD). Demographics and intraoperative and post‐operative outcomes were compared. Histological findings were also analysed and compared. Results: Sixty‐five patients were included in the study. IMD was observed in 39 patients (60%), while CMD was observed in 26 (40%). Male gender was significantly more frequent in CMD ( P = 0.020), and mean age was significantly higher in IMD ( P = 0.025). Body mass index and the American Society of Anesthesiologists score >2 were similar in both groups. Laparoscopy was carried out in 36% of IMD and in 50% of CMD patients ( P = 0.309). A tangential resection was performed in 92% of IMD and 73% of CMD patients ( P = 0.07). No complications related to diverticular resection were found in IMD, while they occurred in 8% of CMD patients ( P = 0.931). Meanly, diverticula were longer when complicated ( P = 0.001). CMD showed significant histological differences and more frequent gastric ectopic mucosa ( P = 0.039). A malignant tumour was incidentally found in IMD. Conclusion: As surgery is mandatory in CMD, the optimal management of IMD remains uncertain. Mucosal abnormalities may favour complications, but these cannot be identified before excision. Stapled diverticulectomy is safe and effective. A surgical approach to IMD may prevent complications at a very low cost.